2010
DOI: 10.1002/maco.200905430
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical corrosion behavior of X80 pipeline steel in a near‐neutral pH solution

Abstract: In this work, the electrochemical corrosion behavior of X80 pipeline steel was investigated in a near-neutral pH solution using electrochemical impedance spectroscopy (EIC) and photo-electrochemical (PEC) measurements as well as X-ray photo-electron spectroscopy (XPS) technique. The effects of hydrogencharging and stress were considered. The results show that the steel is in an active dissolution state, and a layer of corrosion product is formed and deposited on the electrode surface, which is subjected to fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 26 publications
(30 reference statements)
2
11
0
Order By: Relevance
“…The impact of prior deformation on oxidation rates but also on hydrogen evolution, which may cause embrittlement, has been addressed on different materials. Y. Cheng and co-workers [6][7][8][9][10][11] have concluded that strain would promote corrosion specially in the plastic region on high-strength steels [11]. That is in agreement with the mechanoelectrochemical interactions theory, which takes into account the activation of new dislocations in the material.…”
Section: Introductionsupporting
confidence: 67%
“…The impact of prior deformation on oxidation rates but also on hydrogen evolution, which may cause embrittlement, has been addressed on different materials. Y. Cheng and co-workers [6][7][8][9][10][11] have concluded that strain would promote corrosion specially in the plastic region on high-strength steels [11]. That is in agreement with the mechanoelectrochemical interactions theory, which takes into account the activation of new dislocations in the material.…”
Section: Introductionsupporting
confidence: 67%
“…Numerical studies on the behavior of steel at electrochemical corrosion are described in papers [3,[18][19][20][21], but the research did not take into account the impact of local corrosion damage and operating conditions. Thus, even after numerous studies, the need to develop new dependences for assessing the corrosion processes that would take into account local environmental impacts, as well as special features in the operation of oil pipelines, remains largely unresolved.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The majority of papers deal with the presence of carbon dioxide frequently produced by decaying organic matter present in soil. Indeed, this environment is prone to promote corrosion process [7] but some embrittlement was also detected for pipeline steel X65 in slow strain rate test without bubbling carbon dioxide [2].…”
Section: Introductionmentioning
confidence: 98%
“…Then, the simulated ones are used mainly due to their reproducibility in laboratory [1]. We can cite several synthetic solutions [2][3][4] proposed to meet this requirement. These synthetic solutions frequently provoke stress corrosion cracking and are widespread used to evaluate cracking susceptibility of pipeline steels.…”
Section: Introductionmentioning
confidence: 99%